Studi Fenomenologis Kepatuhan Terhadap Standar Akuntansi Pemerintahan Dalam Pelaporan Aset Biologis (Studi Kasus: Organisasi “X”) - Zulkarnain, Arlin; Fanani, Zaenal (IAIN Kudus, 2018)
Implementation of SAP related biological assets generate a polemic against the compliance Financial Statements preparation of public sector organizations in Indonesia. The objectives of this study were to: (i) investigate the phenomenon of understanding/interpretation of public sector management SAP in the preparation of financial statements related to the treatment of biological assets; (ii) reveal the meaning of phenomena gained during the study; (iii) provide inputs based on summarized meanings, in an effort to improve SAP, government accounting policies, or related rules. This research used qualitative approach with the type of phenomenology study. Selected research sites in